44.4k views
25 votes
1. Gloria says the two expressions - (12x + 24) - 9x and -6(x + 1) are equivalent. Is she correc Explain how you know.​

User Kondor
by
5.0k points

1 Answer

7 votes

Answer:

No they aren't equivalent

Explanation:

Let's take each expression

the first one is

- (12x+24) - 9x = -12x -24 -9x = -21x -24 = -3 (7x +8)

the second expression

-6 (x+1) = -6x-6

So they aren't equivalent

User Giladbu
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.